(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
The colonial stamp on the Mapuche people led their cultural productions in large part to the brink the extinction. One of these is monumental wood carving, linked to ceremonial processes in the ancestral culture. However, since the 1990s, this has reappeared together with the processes of recovery and strengthening of the cultural identity, and has rapidly expanded into the old Mapuche territory, invigorating the political and cultural border of this people with two main focuses: as a traditional cultural practice or as an expression of mainly urban modern art. In this framework, this study investigates how the installation of monumental carving is redefining the urban and rural spaces of Güllumapu (Chile). It is maintained that these cultural productions act by semiotizing the cultural contact space, refounding the old wallmapu or Mapuche territory, a process done by inscribing a strong symbolic power that summons a new sense of the historical time-space in the territory through a “production of place” (Appadurai, 1999), articulating categories of cultural and national identity and collaborating in the recovery of the borders by constructing a narrative of the cultural and national identity in an adverse context.